2020
DOI: 10.1186/s41182-020-00267-y
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and its association with CD4 cell count and hemoglobin level among children on antiretroviral therapy in Ethiopia: a systematic review and meta-analysis

Abstract: Background Even though there are advancements in HIV/AIDS prevention and treatment approach, HIV continues to be a global challenge. Pediatrics HIV is one of the challenges in the reduction of child mortality particularly in less developed countries like Ethiopia. Therefore, this study aims to estimate the pooled proportion of child mortality and the effect of hemoglobin level and CD4 cell count among children on antiretroviral therapy in Ethiopia. Method All published were articles searched using PubMed, EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Children presented with hemoglobin level < 10 g/dl had a higher risk of death compared to children presented with hemoglobin level ≥ 10 g/dl. Previous study findings in Ethiopia [ 25 , 29 , 36 , 43 ], Tanzania [ 39 ], and Kenya [ 44 ] had shown that low hemoglobin level was a significant risk of death among children on ART. These could be justified by the fact that when ART is started after a child experiences anemia from HIV infection, the child’s condition may only be partially cured, which could eventually lead to a low quality of life and mortality [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children presented with hemoglobin level < 10 g/dl had a higher risk of death compared to children presented with hemoglobin level ≥ 10 g/dl. Previous study findings in Ethiopia [ 25 , 29 , 36 , 43 ], Tanzania [ 39 ], and Kenya [ 44 ] had shown that low hemoglobin level was a significant risk of death among children on ART. These could be justified by the fact that when ART is started after a child experiences anemia from HIV infection, the child’s condition may only be partially cured, which could eventually lead to a low quality of life and mortality [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition in the form of (wasting, stunting and underweight) is the leading cause of morbidity, low survival and mortality among children infected with HIV particularly in resource-deprived settings [ [11] , [12] , [13] ].In fact, initiation of ART dramatically reduce HIV/AIDS-related morbidity, mortality, and boost survival rate [ [14] , [15] , [16] ]. However, the responses of HIV-infected children for HAART(Highly Active Antiretroviral Therapy) are not similar to adults, because of deleterious impacts of the virus on the immature immunity system, nutritional status and negative consequence on the immunologic response of children living with HIV [ 8 , 17 ].…”
Section: Introductionmentioning
confidence: 99%